Сахарный Кремль: роман / Владимир Сорокин - Сорокин Владимир Георгиевич (Астрель, 2008)
Экземпляры: Селтинская районная библиотека (аб) (20121107) / Инвентарный номер: 199260 / Цена: 214.60 / Авт.знак: С 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6